2021
DOI: 10.3390/jcm10163567
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Gene Co-Expression Network Analysis Combined with Machine Learning Validation to Identify Key Modules and Hub Genes Associated with SARS-CoV-2 Infection

Abstract: The coronavirus disease-2019 (COVID-19) pandemic has caused an enormous loss of lives. Various clinical trials of vaccines and drugs are being conducted worldwide; nevertheless, as of today, no effective drug exists for COVID-19. The identification of key genes and pathways in this disease may lead to finding potential drug targets and biomarkers. Here, we applied weighted gene co-expression network analysis and LIME as an explainable artificial intelligence algorithm to comprehensively characterize transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 107 publications
0
36
0
Order By: Relevance
“…Understanding the biological pathways involved in this disease will ultimately lead to the identification of key genes and pathways which are linked to senescence-aging-COVID-19, thus paving the way to developing novel drug targets and biomarkers for this disease. Indeed, a recent study which combined gene co-expression network analysis with artificial intelligence approaches has identified a potential novel gene signature which may have clinical value in the pathogenesis of COVID-19 [ 278 ].…”
Section: Conclusion and Future Perspectives Of Senescence As A Promising Biomarker And Target In Covid-19mentioning
confidence: 99%
“…Understanding the biological pathways involved in this disease will ultimately lead to the identification of key genes and pathways which are linked to senescence-aging-COVID-19, thus paving the way to developing novel drug targets and biomarkers for this disease. Indeed, a recent study which combined gene co-expression network analysis with artificial intelligence approaches has identified a potential novel gene signature which may have clinical value in the pathogenesis of COVID-19 [ 278 ].…”
Section: Conclusion and Future Perspectives Of Senescence As A Promising Biomarker And Target In Covid-19mentioning
confidence: 99%
“…DEPs were enriched to a Coronavirus disease-COVID-19 pathway by KEGG enrichment analysis. In addition, we referred to previous research strategies, which identified common key genes through enrichment analysis and modules ( 13 ). We also used the COVID-19 KEGG enrichment pathway and the three modules of MCC, Closeness, and Degree to identify key proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We identified key proteins with reference to previous research methods ( 13 ). Cytoscape software was used to calculate the top 30 hub proteins by Degree, Closeness, and MCC methods from PPI networks, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several UM genomic databases are now available for usage by researchers worldwide, which has helped to significantly leverage genomic research in the UM field (Table 3). In 2018, Wan et al used the TCGA genomic data involving 10,975 genes from 80 UM patients [148] and performed weighted gene co-expression network analysis (WGCNA) [156][157][158], a popular method frequently employed to ascertain the potential interactions between genes and phenotypes, which has been successfully utilized in studies in neuroscience [159][160][161], cancer [162][163][164][165] and more recently in COVID-19-applied research [166], among other fields [167]. In a simplistic manner, the WGCNA approach transforms the data of gene expression into modules of co-expression, allowing a better understanding of potential signalling pathways that might be strongly linked with phenotypes of interest [158,167].…”
Section: Gene Signatures As Novel Prognostic Biomarkers In Uveal Mela...mentioning
confidence: 99%